∫ 0 π 1 3 cos θ − 5 2 sin θ + 3 cos θ − 3 d θ = b a π − d c lo g ( f e ) .
If the equation above holds true for positive integers a , b , c , d , e , and f , where a , b , d , e , and f are primes (not necessary distinct), find a + b + c + d + e + f .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Priyanshu Mishra , you have to mention that a , b , c , d , e and f are positive integers. Because b a = 1 3 3 = 6 . 5 1 . 5 = 1 . 3 0 . 3 = . . . , there are infinite solutions.. Most of the times for ratio, you have to mention they are coprime integers bacause 1 3 3 = 2 6 6 = 3 9 9 = . . . , again infinite solution.
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 0 π 1 3 cos θ − 5 2 sin θ + 3 cos θ − 3 d θ = 2 ∫ 0 π 1 3 cos θ − 5 sin θ d θ + 3 ∫ 0 π 1 3 cos θ − 5 cos θ d θ − 3 ∫ 0 π 1 3 cos θ − 5 1 d θ = − 1 3 2 ∫ 8 − 1 8 x 1 d x + 1 3 3 ∫ 0 π 1 3 cos θ − 5 1 3 cos θ − 5 + 5 d θ − 3 ∫ 0 π 1 3 cos θ − 5 1 d θ = − 1 3 2 lo g ∣ x ∣ ∣ ∣ ∣ ∣ 8 − 1 8 + 1 3 3 ∫ 0 π d θ − 1 3 2 4 ∫ 0 π 1 3 cos θ − 5 1 d θ = − 1 3 2 lo g 4 9 + 1 3 3 θ ∣ ∣ ∣ ∣ 0 π − 1 3 2 4 ∫ 0 ∞ 4 − 9 t 2 1 d t = − 1 3 4 lo g 2 3 + 1 3 3 π − 1 3 6 ∫ 0 ∞ ( 2 − 3 t 1 + 2 + 3 t 1 ) d t = 1 3 3 π − 1 3 4 lo g 2 3 − 1 3 6 [ − 3 lo g ∣ 2 − 3 t ∣ + 3 lo g ∣ 2 + 3 t ∣ ] 0 ∞ = 1 3 3 π − 1 3 4 lo g 2 3 + 1 3 2 [ lo g ∣ 2 + 3 t ∣ lo g ∣ 2 − 3 t ∣ ] 0 ∞ = 1 3 3 π − 1 3 4 lo g 2 3 + 0 Let x = 1 3 cos θ − 5 ⟹ d x = − 1 3 sin θ d θ Let t = tan 2 θ ⟹ d t = 2 1 sec 2 2 θ d θ ⟹ cos θ = 1 + t 2 1 − t 2
⟹ a + b + c + d + e + f = 3 + 1 3 + 4 + 1 3 + 3 + 2 = 3 8 .